OLS with multiple high dimensional category dummies - Simen Gaure (University of Oslo, Department of Economics, 2010)
We present some theoretical results which simplifies the estimation of linear models with multiple high-dimensional fixed effects. In particular, we show how to sweep out multiple fixed effects from the normal equations, in analogy with the common within-groups estimator.
Keywords: C13; C33; C60; 330; Method of Alternating Projections; Multiple Fixed Effects; OLS; Methode der kleinsten Quadrate